2000
DOI: 10.1007/s11357-000-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, oxidative DNA damage, and aging

Abstract: Protection from reactive oxygen species (ROS) and from mitochondrial oxidative damage is well known to be necessary to longevity. The relevance of mitochondrial DNA (mtDNA) to aging is suggested by the fact that the two most commonly measured forms of mtDNA damage, deletions and the oxidatively induced lesion 8-oxo-dG, increase with age. The rate of increase is species-specific and correlates with maximum lifespan.It is less clear that failure or inadequacies in the protection from reactive oxygen species (ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 165 publications
(147 reference statements)
0
18
0
Order By: Relevance
“…Age-associated changes in mitochondrial function and mitochondrial content have been implicated in the aging process and have been proposed to be a driving factor for the onset of sarcopenia (Anson and Bohr 2000;Jang et al 2010). An important aspect of mitochondrial health and homeostasis is the mtDNA content and copy number.…”
Section: Discussionmentioning
confidence: 99%
“…Age-associated changes in mitochondrial function and mitochondrial content have been implicated in the aging process and have been proposed to be a driving factor for the onset of sarcopenia (Anson and Bohr 2000;Jang et al 2010). An important aspect of mitochondrial health and homeostasis is the mtDNA content and copy number.…”
Section: Discussionmentioning
confidence: 99%
“…Although both oxidized bases block DNA polymerase, 8-oxodG is more mutagenic and is responsible for the characteristic G→T substitutions [135]. Other oxidative lesions include 8-hydroxyguanine, FAPy-adenine, 8-hydroxyadenine, 5,6-dihydroxyuracil, 5-hdroxyuracil, 5-hydroxycytosine, and 5-hydroxymethyluracil [5,8]. …”
Section: Disparities At the Nuclear Genome Level And Their Role Inmentioning
confidence: 99%
“…In fact, studies in long-lived species showed the presence of reduced oxidative damage [59], reduced mitochondrial free radical production [60], increased antioxidant defences [60] and increased resistance to oxidative stress both in vivo and in vitro [61]. However, a lack of correlation of oxidation with lifespan [62], or even an increase in oxidative damage/stress associated with long lifespan, has also been reported [63].…”
Section: Oxidative Stressmentioning
confidence: 99%